Optimizing glycerosome formulations via an orthogonal experimental design to enhance transdermal triptolide delivery - Zhu Chunyun; Zhang Yongtai; Wu Tong; He Zehui; Guo Teng; Feng Nianping (Acta Pharmaceutica)
Triptolide exerts strong anti-inflammatory and immunomodulatory effects; however, its oral administration might be associated with side effects. Transdermal administration can improve the safety of triptolide. In this study, glycerosomes were prepared as the transdermal vehicle to enhance the transdermal delivery of triptolide. With entrapment efficiency and drug loading as dependent variables, the glycerosome formulation was optimized using an orthogonal experimental design. Phospholipid-to-cholesterol and phospholipid-to-triptolide mass ratios of 30:1 and 5:1, respectively and a glycerol concentration of 20 % (V/V) were used in the optimization. The glycerosomes prepared with the optimized formulation showed good stability, with an average particle size of 153.10 ± 2.69 nm, a zeta potential of –45.73 ± 0.60 mV and an entrapment greater than 75 %. Glycerosomes significantly increased the transdermal delivery of triptolide compared to conventional liposomes. As efficient carriers for the transdermal delivery of drugs, glycerosomes can potentially be used as an alternative to oral triptolide administration.